Relapse-free survival is progressively shortened in a subset of Black patients with immune-mediated TTP treated in the rituximab era - Ayotola Fatola; Michael D. Evans; Jenna Brown; Elizabeth Davis; Andrew Johnson; Ana G. Antun; Andrew M. Farland; Ryan Woods; Ara Metjian; Yara A. Park; Gustaaf de Ridder; Briana Gibson; et al. (Blood Advances)
Abstract: Immune thrombotic thrombocytopenic purpura (iTTP) is a chronically relapsing disorder caused by autoantibody-mediated deficiency of ADAMTS13. Rituximab is frequently administered to prevent relapses, but whether the durability of rituximab effect is maintained with subsequent treatment courses has not been studied. Using the United States Thrombotic Microangiopathy Consortium (USTMA) retrospective iTTP registry, we evaluated clinical relapse-free survival (RFS) with subsequent courses of rituximab treatment in multiply relapsing patients. Separately, we evaluated overall RFS (composite of time to clinical relapse, ADAMTS13 relapse, or preemptive rituximab) in a prospective iTTP cohort from the Johns Hopkins University and the University of Minnesota. In the USTMA registry, median clinical RFS was shorter after the second or subsequent rituximab-treated episode than the first (2.1 vs 6.0 years; P = .04). White patients’ clinical relapse risk after the second and subsequent rituximab courses was not significantly different compared with the first (hazard ratio [HR], 1.86; 95% confidence interval [CI], 0.22-15.80; P = .57), whereas for Black patients, clinical relapse risk was significantly higher after the second or subsequent courses (HR, 2.82; 95% CI, 1.52-5.24; P = .001). In the prospective cohort, overall RFS progressively shortened after each episode of rituximab treatment with the first episode having the longest RFS (2.8 years; interquartile range, 2.0-6.0) and this loss of response durability was most pronounced in Black patients. The durability of rituximab’s effect declines with subsequent treatments, which is more pronounced in Black patients, who may benefit from closer monitoring and alternative immunomodulatory approaches such as maintenance rituximab and consideration of other agents.